Structures of two molluscan hemocyanin genes: Significance for gene evolution - Lieb, Bernhard (National Academy of Sciences, 2001)
We present here the description of genes coding for molluscan hemocyanins. Two distantly related mollusks, Haliotis tuberculata and Octopus dofleini, were studied. The typical architecture of a molluscan hemocyanin subunit, which is a string of seven or eight globular functional units (FUs, designated a to h, about 50 kDa each), is reflected by the gene organization: a series of eight structurally related coding regions in Haliotis, corresponding to FU-a to FU-h, with seven highly variable linker introns of 174 to 3,198 bp length (all in phase 1). In Octopus seven coding regions (FU-a to FU-g) are found, separated by phase 1 introns varying in length from 100 bp to 910 bp. Both genes exhibit typical signal (export) sequences, and in both cases these are interrupted by an additional intron. Each gene also contains an intron between signal peptide and FU-a and in the 3′ untranslated region. Of special relevance for evolutionary considerations are introns interrupting those regions that encode a discrete functional unit. We found that five of the eight FUs in Haliotis each are encoded by a single exon, whereas FU-f, FU-g, and FU-a are encoded by two, three and four exons, respectively. Similarly, in Octopus four of the FUs each correspond to an uninterrupted exon, whereas FU-b, FU-e, and FU-f each contain a single intron. Although the positioning of the introns between FUs is highly conserved in the two mollusks, the introns within FUs show no relationship either in location nor phase. It is proposed that the introns between FUs were generated as the eight-unit polypeptide evolved from a monomeric precursor, and that the internal introns have been added later. A hypothesis for evolution of the ring-like quaternary structure of molluscan hemocyanins is presented.